(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This research aims to find out the impact of the Blue Ocean strategy on increasing the development of marketing performance in Korek Telecom Company - Baghdad. The descriptive analytical approach was used. Also, the questionnaire was utilized as a primary tool in collecting data from the study sample. Where (40) questionnaires were distributed to the respondents of the study population, and 37 questionnaires were retrieved by (92.5%). The research found a statistically significant correlation between the dimensions of the blue ocean strategy and the company’s marketing performance. The study recommended adding new value (innovation) to the company’s services to improve marketing performance.